Optimization Research on the Performance of the RC-DTH Air Hammer Based on Computational Fluid Dynamics - Zihao Liu; Yongjiang Luo; Wenchao He; Rui Tao; Jiangfu He; Yongliang Sun; Hongwei Chen; Qianting Hu (Applied Sciences)
To optimize the performance of the RC-DTH air hammer, a mathematical model detailing each phase of the piston’s movement has been constructed in the present work. Simultaneously, a novel piston structure of the RC-DTH air hammer (Type B) with diverse internal flow has been proposed. The impact performance of the structurally modified RC-DTH hammer is analyzed using Computational Fluid Dynamics (CFD). Additionally, an impact energy testing system for the RC-DTH air hammer is developed to confirm the validity of the numerical simulation results. Research results have shown that enhancing both the intake stroke of the upper chamber (F1) and the outlet stroke of the lower chamber (R2) of the RC-DTH air hammer piston can effectively improve the piston’s impact performance. Conversely, increasing the inlet stroke of the lower chamber (R1) and the outlet stroke of the upper chamber (F2) tends to diminish the piston’s impact performance. Moreover, the quality of the piston influences its striking frequency while having a minimal impact on single-impact energy. As the piston quality increases, the power of the impact diminishes. Once the piston valve stroke parameters are optimized, its impact performance is enhanced by 20.32%. Compared to the GQ89 hammer, the Type B hammer exhibits an 84% increase in impact energy and a 74% increase in impact power.